The nature of social reality : issues in social ontology - Lawson, Tony, 1950- (Abingdon, Oxon : Routledge, 2019)
The social sciences often fail to examine in any systematic way the nature of their subject matter. Demonstrating that this is a central explanation of the widely acknowledged failings of the social sciences, not least of modern economics, this book sets about rectifying matters. Providing an account of the nature of social material in general, as well as of the specific natures of central components of the modern world, such as money and the corporation, Lawson also considers the implications of this theory regarding possibilities for social change. Readers will gain an understanding of how social phenomena, from tables and chairs, to money and firms, and nurses and Presidents are constituted. Fundamental to Lawson's conception is a theory of community-based social positioning, whereby people and things within a community become constituted as components of emergent totalities, with actions governed by the rights and obligations of relevant members of the community. This theory isolates a set of basic principles that will offer the reader an understanding of the natures of all social phenomena. The Nature of Social Reality is for all those, academics and non-academics alike, who wish to gain a grasp on the nature of social phenomena that goes beyond the superficial.
OCLC-licensed vendor bibliographic record.
Keywords: Sociology; SOCIAL SCIENCE / Anthropology / General; SOCIAL SCIENCE / Regional Studies; SOCIAL SCIENCE / Sociology / General; BUSINESS & ECONOMICS / General; BUSINESS & ECONOMICS / Economic History; BUSINESS & ECONOMICS / Economics / General